Uma análise sobre a reprovação escolar nas escolar brasileiras - Barreira, Gil Vicente Esmeraldo (2011)
Analyzing the statistical data taken from the Brazil Test 2007, we performed a study to remove the effect of school failure on student performance, since it serves as a corrective procedure deficit of student learning. So once this treaty deficit, in theory, should show that the average student would be with the same use of other students in the same series. But we noted here, once failed, the student bears this deficit for the other series, in summary, showing how it is used in schools failing to basic education in Brazil is not correcting this deficit, and only perpetuating.